Fe-N-C cathode oxygen reduction catalyst for oxygen etching as well as preparation method and application of Fe-N-C cathode oxygen reduction catalyst

By pyrolysis and oxygen etching treatment on ZIF-8 and synthesized with iron salt, an oxygen etched Fe-N-C cathode oxygen reduction catalyst was prepared, which solved the problems of low active site density of Fe-N-C catalyst and agglomeration of Fe particles, significantly improved the oxygen reduction activity and fuel cell performance of the catalyst.

CN119581583AActive Publication Date: 2025-03-07UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202411852408.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The active site density of Fe-N-C single-atom catalysts is low, making it difficult to adapt to the demand for fuel cells under high power loads, and the agglomeration of Fe particles leads to a decrease in dispersion.

Method used

By performing the first pyrolysis of ZIF-8 in a protective atmosphere, a nitrogen carbon substrate is formed, and then dispersed with superoxide and crown ether in a solvent to form a carbon-oxygen double bond defect, then grinding with iron salt and performing a second pyrolysis, pickling and drying, an oxygen-etched Fe-N-C cathode oxygen reduction catalyst is obtained.

Benefits of technology

This method promotes the dispersion of FeOx particles and the formation of Fe single atomic sites, significantly improves the oxygen reduction activity and fuel cell performance of the catalyst, and is simple in process and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581583A_ABST
    Figure CN119581583A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an oxygen-etched Fe-N-C cathode oxygen reduction catalyst, which comprises the following steps: in a protective atmosphere, performing first pyrolysis on ZIF-8 to obtain a nitrogen-carbon substrate with a regular dodecahedron frame structure; the method comprises the following steps: dispersing a nitrogen-carbon substrate, superoxide and crown ether in a solvent to obtain a turbid liquid, releasing superoxide ions in the turbid liquid, forming a carbon-oxygen double bond defect by the superoxide ions and carbon atoms in the nitrogen-carbon substrate, and centrifuging the turbid liquid to obtain a composite solid; and grinding and mixing the composite solid and iron salt, performing secondary pyrolysis in a protective atmosphere, and performing acid pickling and drying to obtain the oxygen-etched Fe-N-C cathode oxygen reduction catalyst. The invention further provides the Fe-N-C cathode oxygen reduction catalyst obtained through the preparation method and application of the Fe-N-C cathode oxygen reduction catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts and their preparation, and specifically relates to an oxygen-etched Fe-NC cathode oxygen reduction catalyst and a preparation method and application thereof. Background Art

[0002] Fuel cells are known as the most important new energy technology in the 21st century due to their high energy conversion efficiency, clean and environmentally friendly. Among them, the cathode oxygen reduction reaction kinetics of fuel cells is extremely slow, which has become a bottleneck reaction in the operation of the battery. Although the precious metal Pt can effectively catalyze the oxygen reduction reaction, its cost is relatively high. Therefore, the development of non-platinum catalysts is particularly important.

[0003] Fe-NC single-atom catalysts are generally regarded as a strong candidate to replace precious metal Pt-based catalysts and have received widespread attention. However, compared with Pt-based catalysts, the active site density of Fe-NC single-atom catalysts is lower, making it difficult to adapt to the needs of fuel cells under high power loads. This is mainly due to the limited metal atom vacancies on the nitrogen-carbon substrate, which makes it difficult to accommodate high-density Fe single atoms; at the same time, the high specific surface energy of the metal makes it easy for Fe particles to agglomerate under high-temperature sintering conditions in pyrolysis catalysts, further reducing the dispersion of Fe atoms.

[0004] In the related art, the methods to increase the density of Fe single-atom sites mainly include: using vapor deposition technology to allow FeCl3 vapor to directly participate in the transformation of Zn-N4 sites on the nitrogen-carbon substrate to Fe-N4, thereby obtaining a Fe-based single-atom catalyst with high active site density and gas-accessible sites; treating nitrogen-carbon by heating acid reflux and adding dicyandiamide to remove Zn sites in the nitrogen-carbon substrate and increase the nitrogen content of the anchoring metal, and finally obtaining a high-performance Fe-based single-atom catalyst with a metal loading of 7 wt%; using a H2 pyrolysis environment to promote the deoxygenation and dechlorination of nitrogen-carbon and metal precursors, achieving the formation of Fe single-atom sites at a relatively low temperature of 360 °C, avoiding the formation of metal particles at high temperatures.

[0005] Although the single-atom catalysts prepared above have a high loading capacity, there is still a lack of a simple process method based on nitrogen-carbon substrate regulation to achieve high single-atom density. Therefore, finding a Fe-NC single-atom catalyst with a simple process and high active center density has far-reaching practical significance. Summary of the invention

[0006] In view of this, in order to solve at least one technical problem in the related art and other aspects, the present disclosure proposes a method for preparing an oxygen-etched Fe-NC cathode oxygen reduction catalyst, comprising:

[0007] In a protective atmosphere, ZIF-8 is subjected to a first pyrolysis to obtain a nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure;

[0008] The nitrogen-carbon substrate, superoxide and crown ether are dispersed in a solvent to obtain a suspension, in which the superoxide releases superoxide ions, and the superoxide ions form carbon-oxygen double bond defects with carbon atoms in the nitrogen-carbon substrate, and the suspension is centrifuged to obtain a composite solid;

[0009] The composite solid is ground and mixed with iron salt, and then subjected to a second pyrolysis in a protective atmosphere. After acid washing and drying, an oxygen-etched Fe-NC cathode oxygen reduction catalyst is obtained.

[0010] According to an embodiment of the present disclosure, the preparation method of ZIF-8 comprises:

[0011] The methanol solution of zinc nitrate hexahydrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation;

[0012] Wherein, the mass ratio of zinc nitrate hexahydrate to dimethylimidazole is 1:2-1:3.

[0013] According to an embodiment of the present disclosure, in the first pyrolysis, the pyrolysis temperature is 800-1000° C., and the pyrolysis time is 0.5-2 h.

[0014] According to an embodiment of the present disclosure, the superoxide includes KO2, the crown ether includes 18-2 crown ether, the molar ratio of the superoxide to the crown ether is less than 0.9, and the mass ratio of the superoxide to the nitrogen-carbon substrate is 0.3-1.2.

[0015] According to an embodiment of the present disclosure, the iron salt includes any one of FeCl2 and FeSO4, and the mass ratio of the iron salt to the nitrogen-carbon substrate is greater than 0.1.

[0016] According to an embodiment of the present disclosure, in the second pyrolysis, the pyrolysis temperature is 800-1000° C., and the pyrolysis time is 0.5-2 h.

[0017] In another aspect of the present disclosure, a Fe-NC cathode oxygen reduction catalyst obtained by the aforementioned preparation method is also proposed, comprising: a nitrogen-carbon substrate and an active center. The nitrogen-carbon substrate has a regular dodecahedral framework structure, and the surface includes carbon-oxygen double bond defects; the active center is FeN4 loaded in the framework structure.

[0018] According to an embodiment of the present disclosure, the mass fraction of active centers is 7.3 wt %-9.6 wt %.

[0019] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.

[0020] According to the embodiments of the present disclosure, the peak power density of the fuel cell is 1491-1706 mW / cm 2 .

[0021] According to the embodiments of the present disclosure, superoxide ions released in a solution environment by the combination of superoxide and crown ether can achieve mild oxygen etching of the nitrogen-carbon substrate, and then a high-density Fe single-atom catalyst supported by oxygen-etched nitrogen-doped carbon is synthesized by mixing and grinding with iron salts and calcining in an inert atmosphere. This method promotes the FeO x The dispersion of particles and the formation of Fe single atom sites greatly improve the oxygen reduction activity of the catalyst and its performance in fuel cells. The Fe-NC cathode oxygen reduction catalyst prepared by this method has excellent activity and battery performance, and the method proposed in this disclosure is simple and easy to implement, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a spherical aberration electron microscopy image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;

[0023] Figure 2 This is a Fourier transform X-ray extended edge absorption structure (FT-EXAFS) of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;

[0024] Figure 3 The scanning electron microscope images of the oxygen-etched Fe-NC cathode oxygen reduction catalysts prepared in Examples 1, 4, 5, and 12 of the present disclosure, wherein a is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1, b is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 4, c is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 5, and d is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 12;

[0025] Figure 4 The linear sweep voltammetry curve of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Examples 1, 4, 5, and 12 of the present disclosure in a 0.1 M perchloric acid solution;

[0026] Figure 5 This is a polarization curve diagram of the H2-O2 proton exchange membrane fuel cell of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Examples 1, 5, 8, 11, and 12 of the present disclosure under a back pressure of 2 Bar. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0028] The endpoints and any values ​​of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.

[0029] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0030] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0031] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present disclosure shall have the usual meanings understood by persons with ordinary skills in the field to which the present disclosure belongs. If the full text involves descriptions such as "first", "second", etc., the descriptions such as "first", "second", etc. are only used to distinguish similar objects, and cannot be understood as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data described by "first", "second", etc. can be interchangeable under appropriate circumstances.

[0032] Similarly, in order to simplify the present disclosure and help understand one or more of the various disclosed aspects, in the above description of the exemplary embodiments of the present disclosure, the various features of the present disclosure are sometimes grouped together into a single embodiment, figure, or description thereof. The description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" and the like means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0033] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this disclosure.

[0034] In the process of realizing the present disclosure, it was found that nitrogen-doped carbon is the most commonly used carrier for Fe-based single-atom catalysts for acidic oxygen reduction, which often contains a small amount of oxygen. In the process of Fe single atom formation, the metal precursor is often FeO x In the form of migration on the surface of the nitrogen-carbon substrate, the highly electronegative oxygen functional groups are beneficial to reduce FeO x The particle size of the catalyst can be reduced and its dispersion on the substrate surface can be promoted, thereby obtaining a high density of Fe single atom sites during high-temperature pyrolysis. However, the presence of excessive oxygen functional groups may reduce the conductivity and oxygen reduction selectivity of the catalyst, which is not conducive to the activity expression and stability of the catalyst.

[0035] Therefore, the development of high-loading iron single-atom fuel cell cathode catalysts based on oxygen-etched nitrogen-doped carbon supports must adopt appropriate strategies to control the type and content of functional groups in order to obtain excellent acidic oxygen reduction activity and stability.

[0036] The present disclosure proposes a method for preparing an oxygen-etched Fe-NC cathode oxygen reduction catalyst, comprising the following steps S101 to S103:

[0037] Step S101: In a protective atmosphere, ZIF-8 is subjected to a first pyrolysis to obtain a nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure.

[0038] Step S102: dispersing the nitrogen-carbon substrate, superoxide and crown ether in a solvent to obtain a suspension, in which the superoxide releases superoxide ions, and the superoxide ions form carbon-oxygen double bond defects with carbon atoms in the nitrogen-carbon substrate. The suspension is centrifuged to obtain a composite solid.

[0039] In some specific embodiments, the dispersion stirring method is magnetic stirring, the dispersant is dimethyl sulfoxide, the speed is 500-800 rpm, for example, it can be 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., and the time is 12 hours. The separation method is centrifugal separation, the speed is 10000 rpm, and the time is 3 minutes. The drying method is vacuum drying, the drying temperature is 40-80 ° C, for example, it can be 40 ° C, 45 ° C, 50 ° C, 55 ° C, 60 ° C, 65 ° C, 70 ° C, 75 ° C, 80 ° C, etc., and the time is 12 hours.

[0040] Step S103: After grinding and mixing the composite solid and the iron salt, a second pyrolysis is performed in a protective atmosphere, and after acid washing and drying, an oxygen-etched Fe-NC cathode oxygen reduction catalyst is obtained.

[0041] In some specific embodiments, the grinding method is planetary ball milling, the rotation speed is 300 rpm, and the time is 30 min. The pickling method is sulfuric acid pickling, the sulfuric acid concentration is 0.5 M, and the pickling time is 6 h. The separation method after pickling is suction filtration, and the filter cake is washed with 4L ultrapure water. The drying method is vacuum drying, the drying temperature is 40-80 ° C, for example, it can be 40 ° C, 45 ° C, 50 ° C, 55 ° C, 60 ° C, 65 ° C, 70 ° C, 75 ° C, 80 ° C, etc., and the time is 12 h.

[0042] According to the embodiments of the present disclosure, superoxide ions released in a solution environment by the combination of superoxide and crown ether can achieve mild oxygen etching of the nitrogen-carbon substrate, and then a high-density Fe single-atom catalyst supported by oxygen-etched nitrogen-doped carbon is synthesized by mixing and grinding with iron salts and calcining in an inert atmosphere. This method promotes the FeO x The dispersion of particles and the formation of Fe single atom sites greatly improve the oxygen reduction activity of the catalyst and its performance in fuel cells. The Fe-NC cathode oxygen reduction catalyst prepared by this method has excellent activity and battery performance, and the method proposed in this disclosure is simple and easy to implement, and is suitable for large-scale production.

[0043] According to an embodiment of the present disclosure, the preparation method of ZIF-8 comprises:

[0044] The methanol solution of zinc nitrate hexahydrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation;

[0045] The mass ratio of zinc nitrate hexahydrate to dimethylimidazole is 1:2-1:3, for example, 3:6.5.

[0046] In some specific embodiments, Zn(NO3)2·6H2O and 2-methylimidazole are dispersed in methanol at room temperature, preferably by magnetic stirring, and the dispersion time is 5 min. After 5 min of magnetic stirring, clear solutions A and B are obtained; then solutions A and B are mixed, preferably by magnetic stirring at a speed of 500-800 rpm, and stirred at room temperature for 24 h to obtain a suspension; then the suspension is centrifuged, preferably by centrifugation, at a speed of 8000 rpm, for 3 min, and washed three times with methanol, preferably by ultrasonic dispersion in methanol and centrifugation again, at a speed of 10000 rpm, for 3 min; finally, ZIF-8 is dried in an oven at 40-80 °C, preferably by vacuum drying, for 12 h.

[0047] According to an embodiment of the present disclosure, in the first pyrolysis, the pyrolysis method is tubular furnace pyrolysis, the atmosphere is argon, the pyrolysis temperature is 800-1000°C, for example, it can be 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and the pyrolysis time is 0.5-2 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, etc.

[0048] According to an embodiment of the present disclosure, the superoxide includes KO2, the crown ether includes 18-2 crown ether, the molar ratio of superoxide to crown ether is less than 0.9, and the mass ratio of superoxide to nitrogen-carbon substrate is 0.3-1.2, for example, it can be 0.3, 0.6, 0.9, etc.

[0049] According to an embodiment of the present disclosure, the iron salt includes any one of FeCl2 and FeSO4, and the mass ratio of the iron salt to the nitrogen-carbon substrate is greater than 0.1.

[0050] According to an embodiment of the present disclosure, in the second pyrolysis, the pyrolysis temperature is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and the pyrolysis time is 0.5-2 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, etc.

[0051] In another aspect of the present disclosure, a Fe-NC cathode oxygen reduction catalyst obtained by the aforementioned preparation method is also proposed, comprising: a nitrogen-carbon substrate and an active center. The nitrogen-carbon substrate has a regular dodecahedral framework structure, and the surface includes carbon-oxygen double bond defects; the active center is FeN4 loaded in the framework structure.

[0052] According to the embodiments of the present disclosure, compared with the Fe-based single-atom catalyst prepared by the conventional method, the present disclosure introduces oxygen functional groups to disperse Fe atoms, so the catalyst has a higher Fe metal loading and better oxygen reduction activity.

[0053] According to an embodiment of the present disclosure, the mass fraction of the active center is 7.3 wt %-9.6 wt %, for example, it can be 7.3 wt %, 7.4 wt %, 8.0 wt %, 8.8 wt %, 9.6 wt %, etc.

[0054] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.

[0055] According to the embodiments of the present disclosure, the Fe sites of the oxygen-etched Fe-NC cathode oxygen reduction catalyst are well dispersed, and have excellent catalytic activity and fuel cell peak power density.

[0056] According to the embodiments of the present disclosure, the peak power density of the fuel cell is 1491-1706 mW / cm 2 .

[0057] It should be noted that the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in the field without creative work are all within the scope of protection of the present disclosure.

[0058] Example 1

[0059] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0060] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0061] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0062] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst (referred to as O-FeNC). The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 1 was about 9.6 wt%.

[0063] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 1 was characterized by scanning electron microscopy.

[0064] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 1 was characterized by spherical aberration electron microscopy.

[0065] Figure 1 This is a spherical aberration electron microscopy image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.

[0066] like Figure 1 As shown, at the scale of 2 nm, there are highly dense and dispersed Fe single atoms in the catalyst, and there is no agglomeration phenomenon, which further verifies that the preparation method of oxygen-etched Fe-NC cathode oxygen reduction catalyst proposed in the present disclosure can ensure that the active centers are evenly dispersed and not agglomerated under the condition of high active center density (Fe loading 9.6 wt%).

[0067] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 1 was subjected to X-ray absorption spectroscopy analysis.

[0068] Figure 2 This is the Fourier transform X-ray extended edge absorption structure (FT-EXAFS) of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.

[0069] like Figure 2 As shown, the oxygen-etched Fe-NC cathode oxygen reduction catalyst (O-FeNC catalyst for short) prepared in Example 1 only has Fe-N / O bonds with a bond length of about 1.4 Å in the first shell, but does not have Fe-Fe bonds with a bond length of 2.1-2.3 Å in the second shell. This further verifies that the preparation method of the oxygen-etched Fe-NC cathode oxygen reduction catalyst proposed in the present disclosure can ensure that the active centers are evenly dispersed and not agglomerated under the condition of high active center density.

[0070] Example 2

[0071] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0072] The first composite solid was pyrolyzed at 850 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0073] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0074] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 2 was about 8.0 wt%.

[0075] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 2 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0076] Example 3

[0077] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0078] The first composite solid was pyrolyzed at 1000°C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0079] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0080] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 3 was about 8.2 wt%.

[0081] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 3 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0082] Example 4

[0083] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0084] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0085] 100 mg of the second composite solid, 29.7 mg of KO2, and 132.2 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0086] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 4 was about 8.6 wt%.

[0087] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 4 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0088] Example 5

[0089] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0090] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0091] 100 mg of the second composite solid, 118.6 mg of KO2, and 528.6 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0092] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 5 was about 9.3 wt%.

[0093] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 5 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0094] Example 6

[0095] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0096] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0097] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0098] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 800 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 6 was about 9.1 wt%.

[0099] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 6 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0100] Example 7

[0101] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0102] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0103] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0104] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 1000 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 7 was about 8.0 wt%.

[0105] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 7 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0106] Example 8

[0107] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0108] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0109] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0110] 100 mg of the third composite solid was mixed with 20 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 2 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 8 was about 7.9 wt%.

[0111] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 8 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0112] Example 9

[0113] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0114] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0115] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0116] 100 mg of the third composite solid was mixed with 38.4 mg of FeSO4·7H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 9 was about 7.3 wt%.

[0117] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 9 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0118] Example 10

[0119] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0120] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0121] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0122] 100 mg of the third composite solid was mixed with 5 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 10 was about 7.4 wt%.

[0123] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 10 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0124] Embodiment 11

[0125] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0126] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0127] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0128] 100 mg of the third composite solid was mixed with 10 mg of FeCl2·4H2O, and the mixture was subjected to planetary ball milling at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain a fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum drying oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 11 was about 8.9 wt%.

[0129] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 11 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0130] Example 12

[0131] At room temperature, 3.5 g of Zn(NO3)2·6H2O was dispersed in 40 mL of methanol and 6 g of 2-methylimidazole was dispersed in 80 mL of methanol, respectively. After magnetic stirring for 5 min, clear solutions A and B were obtained. Solutions A and B were mixed and stirred at room temperature for 24 h to obtain a first suspension. The first suspension was centrifuged at 8000 rpm for 3 min, and then washed three times with methanol at 10000 rpm for 3 min. It was dried in a vacuum drying oven at 60 °C for 12 h to obtain ZIF-8, which was recorded as the first composite solid.

[0132] The first composite solid was pyrolyzed at 950 °C under argon for 1 h to obtain a nitrogen-carbon substrate, which was recorded as the second composite solid.

[0133] 100 mg of the second composite solid, 59.3 mg of KO2, and 264.3 mg of 18-2 crown ether were dispersed in 100 mL of dimethyl sulfoxide solution and magnetically stirred for 12 h to obtain a second suspension; the second suspension was centrifuged and dried in a vacuum drying oven at 60 °C for 12 h to obtain a third composite solid.

[0134] 100 mg of the third composite solid was mixed with 40 mg of FeCl2·4H2O, and the mixture was milled at 300 rpm for 30 min, and then pyrolyzed at 900 °C under argon for 1 h to obtain the fourth composite solid. The fourth composite solid was acid-washed with 0.5 M sulfuric acid for 6 h, and then filtered and the filter cake was washed with 4 L of ultrapure water. The filter cake was dried in a vacuum oven at 60 °C for 12 h to obtain an oxygen-etched Fe-NC cathode oxygen reduction catalyst. The Fe element loading of the oxygen-etched Fe-NC catalyst prepared in Example 12 was about 9.2 wt%.

[0135] The oxygen-etched Fe-NC cathode oxygen reduction catalyst of Example 12 was subjected to spherical aberration electron microscopy, X-ray absorption spectroscopy, linear scanning voltammetry, and fuel cell polarization analysis, and the results were similar to those of Example 1.

[0136] Figure 3 These are scanning electron microscope images of the oxygen-etched Fe-NC cathode oxygen reduction catalysts prepared in Examples 1, 4, 5, and 12 of the present disclosure, wherein a is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1, b is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 4, c is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 5, and d is a scanning electron microscope image of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 12.

[0137] like Figure 3As shown, at a scale of 100 nm, the catalyst particles are regular dodecahedral framework structures with a diameter of about 200 nm, and the material prepared in Example 1 does not show obvious particles at this scale.

[0138] The oxygen-etched Fe-NC cathode oxygen reduction catalysts prepared in Examples 1, 4, 5, and 12 were subjected to linear sweep voltammetry tests in 0.1 M perchloric acid solution.

[0139] Figure 4 The linear sweep voltammogram of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Examples 1, 4, 5, and 12 of the present disclosure in a 0.1 M perchloric acid solution.

[0140] like Figure 4 As shown, the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 exhibits excellent acidic oxygen reduction activity, with a half-wave potential of 0.881 V, a half-wave potential of 0.875 V in Example 4, a half-wave potential of 0.874 V in Example 5, and a half-wave potential of 0.861 V in Example 12, all of which are superior to commercial platinum-carbon catalysts (Pt / C, 0.86 V) and traditional Fe-NC cathode oxygen reduction catalysts (FeNC, 0.825 V). It is proved that the oxygen-etched Fe-NC cathode oxygen reduction catalyst obtained in Example 1 has high electrode reaction activity in the electrochemical reaction and can more effectively promote the electrochemical reaction. The optimal catalyst preparation parameters should be as shown in Example 1.

[0141] The oxygen-etched Fe-NC cathode oxygen reduction catalysts prepared in Examples 1, 5, 8, 11, and 12 were subjected to H2-O2 proton exchange membrane fuel cell polarization tests at a back pressure of 2 Bar.

[0142] Figure 5 This is a polarization curve diagram of the H2-O2 proton exchange membrane fuel cell of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Examples 1, 5, 8, 11, and 12 of the present disclosure under a back pressure of 2 Bar.

[0143] like Figure 5 As shown in Figure 1, the peak power density of the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure is 1706 mW / cm 2 The peak power density of Example 5 is 1491 mW / cm 2 The peak power density of Example 8 is 1553 mW / cm 2 The peak power density of Example 11 is 1631 mW / cm 2 The peak power density of Example 12 is 1627 mW / cm 2The peak power density of the conventional Fe-NC cathode oxygen reduction catalyst is 783 mW / cm 2 It can be seen that the oxygen-etched Fe-NC cathode oxygen reduction catalyst prepared in Example 1 exhibits excellent peak power density. The optimal catalyst preparation parameters should be as shown in Example 1.

[0144] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present disclosure in detail. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A method for preparing an oxygen-etched Fe-NC cathode oxygen reduction catalyst, comprising: In a protective atmosphere, ZIF-8 is subjected to a first pyrolysis to obtain a nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure; Dispersing the nitrogen-carbon substrate, superoxide and crown ether in a solvent to obtain a suspension, wherein the superoxide releases superoxide ions in the suspension, and the superoxide ions form carbon-oxygen double bond defects with carbon atoms in the nitrogen-carbon substrate, and centrifuging the suspension to obtain a composite solid; The composite solid is ground and mixed with iron salt, and then pyrolyzed for the second time in a protective atmosphere. After acid washing and drying, an oxygen-etched Fe-NC cathode oxygen reduction catalyst is obtained.

2. The preparation method according to claim 1, wherein The preparation method of ZIF-8 comprises: The methanol solution of zinc nitrate hexahydrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation; Wherein, the mass ratio of the zinc nitrate hexahydrate to dimethylimidazole is 1:2-1:

3.

3. The preparation method according to claim 1, wherein In the first pyrolysis, the pyrolysis temperature is 800-1000° C. and the pyrolysis time is 0.5-2 h.

4. The preparation method according to claim 1, wherein The superoxide includes KO2, the crown ether includes 18-2 crown ether, the molar ratio of the superoxide to the crown ether is less than 0.9, and the mass ratio of the superoxide to the nitrogen-carbon substrate is 0.3-1.

2.

5. The preparation method according to claim 1, wherein The iron salt includes any one of FeCl2 and FeSO4, and the mass ratio of the iron salt to the nitrogen-carbon substrate is greater than 0.

1.

6. The preparation method according to claim 1, wherein In the second pyrolysis, the pyrolysis temperature is 800-1000° C. and the pyrolysis time is 0.5-2 h.

7. A Fe-NC cathode oxygen reduction catalyst obtained by the preparation method according to any one of claims 1 to 6, comprising: A nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure, wherein a surface of the nitrogen-carbon substrate includes carbon-oxygen double bond defects; Active center, the active center is FeN4 loaded in the framework structure.

8. The Fe-NC cathode oxygen reduction catalyst according to claim 7, wherein: The mass fraction of the active center is 7.3 wt %-9.6 wt %.

9. Use of the Fe-NC cathode oxygen reduction catalyst according to any one of claims 7 or 8 in a fuel cell.

10. The use according to claim 9, wherein: The peak power density of the fuel cell is 1491-1706 mW / cm 2 .

Citation Information

Patent Citations

  • Synthetic method capable of systematically regulating atom number of supported Fe atom clusters

    CN109499602A

  • ZIF-8-derived hollow Fe / Cu-N-C type oxygen reduction catalyst and preparation method and application thereof

    CN110752380A

  • Fuel cell catalyst with high-density active sites and preparation method of fuel cell catalyst

    CN114447353A

  • Metal-doped mesoporous carbon-based catalyst as well as preparation method and application thereof

    CN114797847A

  • Three-dimensional ordered porous oxygen reduction catalyst as well as preparation method and application thereof

    CN116137331A

Cited By

  • Pickling defect engineering modified iron monatomic catalyst as well as preparation method and application thereof

    CN121972206A